2014
DOI: 10.17219/acem/37356
|View full text |Cite
|
Sign up to set email alerts
|

The Lifetime Prevalence of Anxiety Disorders Among Patients with Irritable Bowel Syndrome

Abstract: Background. The prevalence of irritable bowel syndrome (IBS), the most common functional gastrointestinal disorder, ranges from 10% to 20% in the general population. It is estimated that from 40% to 90% of persons with a diagnosis of IBS suffer from mental disorders, mainly anxiety and depressive disorders. Objectives. The aim of the study was to assess the lifetime prevalence of anxiety disorders in IBS patients and to compare it with the prevalence of these disorders in a control group of patients with gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 27 publications
(37 reference statements)
0
19
0
5
Order By: Relevance
“…These individuals had a lifetime odds ratio of 2.08 (95% CI: 1.34 - 3.24) for acquiring mood disorders and 1.86 (95% CI: 1.08 - 3.21) for anxiety disorders in their study. In a study in 2014, Grzesiak and colleagues 27 evaluated the lifetime prevalence of anxiety and depressive disorders among patients with IBS and patients with gastric reflux using the ICD-10 criteria. They found that anxiety disorders existed in about 47% of the patients with IBS.…”
Section: Discussionmentioning
confidence: 99%
“…These individuals had a lifetime odds ratio of 2.08 (95% CI: 1.34 - 3.24) for acquiring mood disorders and 1.86 (95% CI: 1.08 - 3.21) for anxiety disorders in their study. In a study in 2014, Grzesiak and colleagues 27 evaluated the lifetime prevalence of anxiety and depressive disorders among patients with IBS and patients with gastric reflux using the ICD-10 criteria. They found that anxiety disorders existed in about 47% of the patients with IBS.…”
Section: Discussionmentioning
confidence: 99%
“…The major impact of IBS is on quality of life, with several studies showing this to be comparable to patients with migraines and asthma . Many patients experience a fear of symptoms and even social phobia, in which an excessive fear of symptoms leads to avoidance of social situations . For this reason, it may be that self‐assessment of symptoms may be the most appropriate for clinical management as treatments are aimed to improve symptoms to the patients’ level of satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Many patients experience a fear of symptoms 17 and even social phobia, in which an excessive fear of symptoms leads to avoidance of social situations. 18 For this reason, it may be that selfassessment of symptoms may be the most appropriate for clinical management as treatments are aimed to improve symptoms to the patients' level of satisfaction. While patients' interpretation of symptoms is thus clearly important, discrepancies between diarrhea definitions are an important confounder in research, where homogeneity is essential for accurate endpoints and outcomes.…”
Section: Fecal Water Content Across Different Dietsmentioning
confidence: 99%
“…This can affect perception and interpretation of symptoms, especially pain, and may result in state‐congruent and ecological recall bias in retrospective questionnaires . Affective comorbidity such as anxiety disorders, are prevalent in IBS patients and the presence of psychological comorbidity may contribute to a distorted perception and memory of GI symptoms as well . Furthermore, the inability to record temporal dynamics of symptoms renders retrospective questionnaires less suitable for measurement of symptoms fluctuating over time.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Affective comorbidity such as anxiety disorders, are prevalent in IBS patients and the presence of psychological comorbidity may contribute to a distorted perception and memory of GI symptoms as well. 10,11 Furthermore, the inability to record temporal dynamics of symptoms renders retrospective questionnaires less suitable for measurement of symptoms fluctuating over time. Finally, it has been shown that paper diaries are subject to low compliance rates, as low as approximately 10%, due to backfilling of questionnaires.…”
Section: Introductionmentioning
confidence: 99%